Multicolor mapping of the cardiomyocyte proliferation dynamics that construct the atrium - Foglia, Matthew J. (Development, 2016)
The orchestrated division of cardiomyocytes assembles heart chambers of distinct morphology. To understand the structural divergence of the cardiac chambers, we determined the contributions of individual embryonic cardiomyocytes to the atrium in zebrafish by multicolor fate-mapping and we compare our analysis to the established proliferation dynamics of ventricular cardiomyocytes. We find that most atrial cardiomyocytes become rod-shaped in the second week of life, generating a single-muscle-cell-thick myocardial wall with a striking webbed morphology. Inner pectinate myofibers form mainly by direct branching, unlike delamination events that create ventricular trabeculae. Thus, muscle clones assembling the atrial chamber can extend from wall to lumen. As zebrafish mature, atrial wall cardiomyocytes proliferate laterally to generate cohesive patches of diverse shapes and sizes, frequently with dominant clones that comprise 20-30% of the wall area. A subpopulation of cardiomyocytes that transiently express atrial myosin heavy chain (amhc) contributes substantially to specific regions of the ventricle, suggesting an unappreciated level of plasticity during chamber formation. Our findings reveal proliferation dynamics and fate decisions of cardiomyocytes that produce the distinct architecture of the atrium.